23+12y-4=0

Combine 12 and y.

23+y2-4=0

To write –41 as a fraction with a common denominator, multiply by 33.

y2+23+-41⋅33=0

Write each expression with a common denominator of 3, by multiplying each by an appropriate factor of 1.

Combine.

y2+23+-4⋅31⋅3=0

Multiply 3 by 1.

y2+23+-4⋅33=0

y2+23+-4⋅33=0

Combine the numerators over the common denominator.

y2+2-4⋅33=0

Simplify the numerator.

Multiply -4 by 3.

y2+2-123=0

Subtract 12 from 2.

y2+-103=0

y2+-103=0

Move the negative in front of the fraction.

y2-103=0

y2-103=0

Add 103 to both sides of the equation.

y2=103

Multiply both sides of the equation by 2.

2⋅y2=2⋅103

Cancel the common factor of 2.

Cancel the common factor.

2⋅y2=2⋅103

Rewrite the expression.

y=2⋅103

y=2⋅103

Multiply 2(103).

Combine 2 and 103.

y=2⋅103

Multiply 2 by 10.

y=203

y=203

y=203

The result can be shown in multiple forms.

Exact Form:

y=203

Decimal Form:

y=6.6‾

Mixed Number Form:

y=623

Solve for Y 2/3+1/2y-4=0